Sustainable transformation: climate and economic analyses for renewable energies at a university - Pinto, Aline Cristina Marcelino; Lermen, Fernando Henrique; Farinhas, Felipe Neves; Skrzyzowski, Vinicius dos Santos; Fernandes, Sânia da Costa (Brazilian Journal of Production Engineering, 2024)
Energy plays a crucial role in economic growth and sustainability, making the promotion of renewable sources essential. With buildings consuming approximately 30% of global energy, the implementation of sustainable practices on university campuses, seen as "miniature cities," is gaining prominence. Universities have a duty to lead in adopting renewable energy, promoting clean consumption and sustainability. This study employs multivariate statistical analyses and economic feasibility assessments to identify the most promising renewable energy source for the campuses of Paraná State University. Curitiba stands out for the potential of photovoltaic solar energy, provided it is combined with efficient storage. Paranavaí benefits from high solar radiation, while União da Vitória shows feasibility for both solar and hydroelectric energy, depending on the availability of water resources. This study offers a pioneering approach to assessing the feasibility of renewable energy adoption on different university campuses. By simultaneously considering multiple variables, it provides valuable insights for university administrators and infrastructure managers that can facilitate an efficient and economical transition to renewable energy sources.
Keywords: Sustainability; Renewable energies; Climate analysis; Economic analysis